Early, Chronic, and Acute Cannabis Exposure and Their Relationship With Cognitive and Behavioral Harms - López-Pelayo, Hugo; Campeny, Eugènia; Oliveras, Clara; Rehm, Jürgen; Manthey, Jakob; Gual, Antoni; Balcells-Olivero, Maria de las Mercedes (Frontiers in Psychiatry, 2021)
Background. Cannabis is the third most consumed drug worldwide. Thus, healthcare providers should be able to identify users who are in need for an intervention. This study aims to explore the relationship of acute, chronic and early exposure (AE, CE, EE) to cannabis with cognitive and behavioral harms (CBH), as a first step towards defining risky cannabis use criteria. Methods. Adults living in Spain, who used cannabis at least once during the last year answered an online survey about cannabis use and health-related harms. Cannabis use was assessed in five dimensions: quantity on use days during the last 30 days (AE), frequency of use in the last month (AE), years of regular use (YRCU) (CE), age of first use (AOf) (EE) and age of onset of regular use (AOr) (EE). CBH indicators included validated instruments and custom-made items. Pearson correlations were calculated for continuous variables and t-Student tests for independent samples were calculated for categorical variables. Effect sizes were calculated for each of the five dimensions of use (Cohen’s d or r Pearson correlation) and harm outcome. Classification and Regression Trees (CART) analyses were performed for those dependent variables (harms) significantly associated with at least two dimensions of cannabis use patterns. Lastly, logistic binary analyses were conducted for each harm outcome. Results. 1,606 out of 2,124 respondents (75.6%) reported at least one harm outcome (mean 1.8 and SD1.5). In our sample using cannabis on 3 out of 4 days was associated with an 8-fold probability of scoring 4+ on the Severity Dependence Scale (OR 8.33, CI95% 4.91-14.16, p<0.001), which is indicative of a cannabis use disorder. Also, a start of regular cannabis use before the age of 25 combined with using cannabis at least once per month was associated with a higher probability of risky alcohol use (OR 1.33 CI95% 1.12-1.57, p=0.001). Besides, a start of regular cannabis use before the age of 18 combined with a period of regular use of at least 7.5 years was associated with a higher probability of reporting a motor vehicle accident (OR 1.81 CI 95% 1.41-2.32, p<0.0001).